Percepção de gestantes acerca da saúde bucal na gravidez - Sampaio, Emilyn Beserra (2019)
The pregnancy is a strategic period in a family life. The Family Health Team has included dental care in prenatal care, thus guaranteeing the possibility of a comprehensive health care. Education on oral health during the gestational period is very important, since during pregnancy women are eager to receive new knowledge and receptive to changes in certain behavioral patterns that may have positive consequences on the health of the baby and the whole family. In that perspective, the objective of the current study is to know the perception of pregnant women attended at UAPS Luís Costa, regarding prevention, opportunities for dental treatments and possible oral changes developed during the gestational period. As to the methodological path, it is a study with a qualitative, observational, exploratory and cross-sectional approach in the modality of case study. Beyond that, the research followed the precepts of Resolution 466/12. The interviews were conducted with 10 pregnant women, defined by saturation criteria. It was possible to identify the guidelines they receive and realize that their general knowledge about oral health during pregnancy is still very precarious and thus revealing that prevention and treatment actions are still very necessary. We found that the care practices of the pregnant women themselves with their oral health are irregular, but in their own assessment, the dental prenatal consultation was very satisfactory.